#### Answer

x=-2

#### Work Step by Step

Simplifying
6(x + 7) + -5(x + 8) = 0
Reorder the terms:
6(7 + x) + -5(x + 8) = 0
(7 * 6 + x * 6) + -5(x + 8) = 0
(42 + 6x) + -5(x + 8) = 0
Reorder the terms:
42 + 6x + -5(8 + x) = 0
42 + 6x + (8 * -5 + x * -5) = 0
42 + 6x + (-40 + -5x) = 0
Reorder the terms:
42 + -40 + 6x + -5x = 0
Combine like terms: 42 + -40 = 2
2 + 6x + -5x = 0
Combine like terms: 6x + -5x = 1x
2 + 1x = 0
Solving
2 + 1x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + 1x = 0 + -2
Combine like terms: 2 + -2 = 0
0 + 1x = 0 + -2
1x = 0 + -2
Combine like terms: 0 + -2 = -2
1x = -2
Divide each side by '1'.
x = -2
Simplifying
x = -2